تمارين معادلات الاولى


                                                                                        

تمارين معادلات الاولى      

                                                             -6b + 6 + 4b = 3b + 11                         (1  

     

                                        3(x-8)-2x+7+5x =0                         (2      
 
            
                            5x -(2x + 1) = 2 - 3(x + 2)                            (3     
 
 
             %282x%2F3%29-%28%28x-5%29%2F5%29=2-%28%285%2B3x%29%2F15%29                       (4     
 
                                                                             
                                4+3x-6 = 3x+2-x                       
(5   
 
   
                             19-(2x+3)=2(x+3)+x                          (6  
 
 
   2(3x-1)-5(2x+3)=4x-7                      (7  
 
 
أجوبة           
Welcome To My Website
hassan.ab.ma © 2017.Free Web Site